Genre Across The Curriculum - Herrington, Anne; Moran, Charles (University Press of Colorado, 2005)
Genre across the Curriculum will function as a "good" textbook, one not for the student, but for the teacher, and one with an eye on the context of writing. Here you will find models of practice, descriptions written by teachers who have integrated the teaching of genre into their pedagogy in ways that both support and empower the student writer. While authors here look at courses across disciplines and across a range of genres, they are similar in presenting genre as situated within specific classrooms, disciplines, and institutions. Their assignments embody the pedagogy of a particular teacher, and student responses here embody students' prior experiences with writing. In each chapter, the authors define a particular genre, define the learning goals implicit in assigning that genre, explain how they help their students work through the assignment, and, finally, discuss how they evaluate the writing their students do in response to their teaching.